Technical Cooperation for Pollinator Conservation and the Promotion of Sustainable Agricultural Practices in Latin America and the Caribbean (2025)
The document outlines a technical cooperation project led by IICA and partners, focused on pollinator conservation and the promotion of sustainable agricultural practices in Latin America and the Caribbean. It emphasizes the implementation of best practices in pilot landscapes, including Chapada Diamantina in Brazil, aiming to mitigate pollinator loss through integrated governance, capacity building, and community engagement. The project seeks to strengthen public policies, foster sustainable value chains, and develop a catalog of pollinator-friendly practices. Additionally, it promotes international cooperation and multi-stakeholder dialogues to enhance biodiversity conservation and food security across the region.